Workload with Documentation Nursing Care in the Patient Room - Benny Harry Leksmon Situmorang; Viere Allanled Siauta; Elin Puspitasari; Iin Octaviana Hutagaol (Sarana Ilmu Indonesia (salnesia), 2023)
Nursing documentation is part of a record action of accurate written evidence carried out by nurses during nursing activities high workloads can affect complete nursing documentation. The purpose of the research was to analyze the relationship of the workload with the documentation of nursing care in the nursing room in RSUD Tora Belo District Sigi. This research was a quantitative study with a cross sectional approach. The population was a cement and ebony nurses with a total of 34 subjects. Research tools for this research were the workload questionnaires and document observation panel. The sampling technique used is the total sampling technique. Its free variable was a workload and its bonded variable was a data analysis document used spearman test. Univariat result obtained heavy workload of 18 subjects 52,9 %, incomplete care record of 31 subjects 91,2 %. Two variable analysis shows that there's a workload link with a nursing system in the hospital in RSUD Tora Belo District Sigi which was p-value=0,035 (p-value<0,05). While correlation value of 0,36 indicated a medium relationship with positive correlation value. The conclusion of this study is that there's a workload link to the documentation of nursing care in the nursing room in RSUD Tora Belo District Sigi.